(untitled) (London Journal of Engineering Research, 2026)
This study used a Sanlien VW-dot data logger and vibrating-wire electronic piezometers to record continuous groundwater level data from monitoring wells at one-hour intervals. We attempted to stratify the subsurface by analyzing changes in groundwater level decline rates. The observations indicate that the decline rate (slope) generally decreases with depth, which may reflect lower fracture density and connectivity in rock masses or increased compactness of deeper soil layers. The stratification process selected segments with regular decline rates and grouped segments with similar slopes into the same layer. Better layer boundaries were calibrated using multiple line segments with different slope values and depth ranges. Regular decline slopes usually appear several hours after rainfall and are related to local geology, hydrology, and lithology. Because fracture saturation and seepage-equilibrium times differ, the onset time of regular slopes also differs. During stratification, obvious interference from subsequent rainfall should be avoided. In addition, some boundaries still show identifiable differences in variability, so sublayers can be further defined; the causes of these differences are discussed in the paper. Overall, decline-rate stratification generally decreases with depth and is related to weathering, effective fracture ratio, or RQD from shallow to deep strata. Engineering factors, such as horizontal drainage from catch wells and the compaction quality of backfilled trench areas after underground pipeline works, can also affect layer thickness.